Future Directions for Public Health Education Reforms in India - Zodpey, Sanjay P.; Negandhi, Himanshu; Yeravdekar, Rajiv (Frontiers in Public Health, 2014)
Health systems globally are experiencing a shortage of competent public health professionals. Public health education across developing countries is stretched by capacity generation and maintaining an adequate ‘standard’ and ‘quality’ of their graduate product. We analyzed the Indian public health education scenario using the institutional and instructional reforms framework advanced by the Lancet Commission report on Education of Health Professionals. The emergence of a new century necessitates a re-visit on the institutional and instructional challenges surrounding public health education. Currently, there is neither an accreditation council nor a formal structure or system of collaboration between academic stakeholders. Health systems have little say in health professional training with limited dialogue between health systems and public health education institutions. Despite a recognized shortfall of public health professionals, there are limited job opportunities for public health graduates within the health system and absence of a structured career pathway for them. Public health institutions need to evolve strategies to prevent faculty attrition. A structured development program in teaching-learning methods and pedagogy is the need of the hour.